Issues and Challenges for Teaching Successful Programming Courses at National Secondary Schools of Malaysia - Salleh F.H.M.; Dewi D.A.; Liyana N.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Budget control; Computer systems programming; Curricula; Learning systems; Students; Education ministries; Education policies; Issues and challenges; Programming course; Programming skills; Self learning system; Teaching and learning; Teaching effectiveness; Teaching